Resource Analysis of Medicinal Herbs of Padder Valley in J&K - Singh, Pardeep; Sharma, A. K. (Indian Forester, 2012)
This paper highlights the richness of medicinal herbs in the Padder valley of J & K state. The phytosociological studies were undertaken by stratified random sampling and recording of the herbs with medicinal value. A total of 34 medicinal herbs belonging to 18 families were recorded. Bunium periscum was the dominant herb in all the four sites of the study area.